ANALISIS TEORETIS IMPLEMENTASI PJBL SEBAGAI UPAYA PENGUATAN LITERASI SAINS TENTANG EKOSISTEM BAGI SISWA KELAS V SD - Khoirul Anam; Iswatiningsih, Daroe; Ahmad Salim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This theoretical study addresses the persistently low science literacy among Indonesian elementary students, particularly the tendency to teach complex ecosystem concepts through rote memorization rather than systemic understanding. The research aims to theoretically analyze how the syntax of Project-Based Learning (PjBL) strengthens science literacy in fifth-grade students. Employing a systematic literature review and qualitative content analysis, this study synthesizes peer-reviewed journals, pedagogical references, and official curriculum documents published between 2019 and 2024. The findings reveal a systematic alignment between PjBL phases and OECD-PISA science literacy indicators: formulating essential questions enhances the ability to explain scientific phenomena, project planning develops competency in designing scientific inquiry, and process monitoring cultivates critical data interpretation. Concrete, context-driven projects function as cognitive bridges that enable students in the concrete-operational stage to construct systemic ecosystem understanding through authentic investigation. The synthesis confirms that PjBL theoretically transforms passive content retention into active scientific reasoning, provided structured scaffolding and authentic environmental problems are maintained. This conceptual blueprint offers a foundation for educators and researchers to design inquiry-oriented ecosystem learning that moves beyond craft-making. Future empirical validation through field studies is recommended.